Position of the greater trochanter and functional femoral antetorsion: Which factors matter in the management of femoral antetorsion disorders?. (June 2018) - Batailler, C.; Weidner, J.; Wyatt, M.; Dalmay, F.; Beck, M.
Abstract : Aims: The primary aim of this study was to define and quantify three new measurements to indicate the position of the greater trochanter. Secondary aims were to define 'functional antetorsion' as it relates to abductor function in populations both with and without torsional abnormality. Patients and Methods: Three new measurements, functional antetorsion, posterior tilt, and posterior translation of the greater trochanter, were assessed from 61 CT scans of cadaveric femurs, and their reliability determined. These measurements and their relationships were also evaluated in three groups of patients: a control group (n = 22), a 'high-antetorsion' group (n = 22) and a 'low-antetorsion' group (n = 10). Results: In the cadaver group, the mean anatomical antetorsion was 14.7° (sd 8.5; 0 to 36.5) and the functional antetorsion 21.5° (sd 8.1; 3.6 to 44.3): the posterior tilt was 73.3° (sd 10.8; 46.9 to 88.7) and the posterior translation 0.59 (sd 0.2; 0.2 to 0.9). These measurements had excellent intra and interobserver agreement with a range from 0.93 to 0.99. When the anatomical antetorsion decreased, the greater trochanter was more tilted and translated posteriorly in relation to the axis of the femoral neck, and the difference between functional and anatomical antetorsion increased. The results the three patient groups were similar to those of the cadaver group. Conclusion: The position of the greater trochanter and functional antetorsion varied with anatomical antetorsion. In the surgical management of femoral retrotorsion, subtrochanteric osteotomy can result in an excessively posterior position of the greater trochanter and an increase in functional antetorsion. Cite this article: Bone Joint J 2018;100-B:712–19.